Peak Width of Skeletonized Mean Diffusivity as a Marker of Diffuse Cerebrovascular Damage - Low, Audrey; Mak, Elijah; Stefaniak, James D.; Malpetti, Maura; Nicastro, Nicolas; Savulich, George; Chouliaras, Leonidas; Markus, Hugh S.; Rowe, James B.; O’Brien, John T. (Frontiers in Neuroscience, 2020)
Background: The peak width of skeletonized mean diffusivity (PSMD) has been proposed as a fully-automated imaging marker of relevance to cerebral small vessel disease (SVD). We assessed PSMD in relation to conventional SVD markers, global measures of neurodegeneration, and cognition. Methods: 145 participants underwent 3T brain MRI and cognitive assessment. 112 were patients with mild cognitive impairment, Alzheimer’s disease, progressive supranuclear palsy, dementia with Lewy bodies, or frontotemporal dementia. PSMD, SVD burden (white matter hyperintensities (WMH), enlarged perivascular spaces, microbleeds, lacunes), average mean diffusivity (MD), grey matter (GM), white matter (WM), and total intracranial volume were quantified. Robust linear regression was conducted to examine associations between variables. Dominance analysis assessed the relative importance of markers in predicting various outcomes. Regional analyses examined spatial overlap between PSMD and WMH. Results: PSMD was associated with global and regional SVD measures, especially WMH and microbleeds. Dominance analysis demonstrated that amongst SVD markers, WMH was the strongest predictor of PSMD. Furthermore, PSMD was more closely associated to WMH than with GM and WM volumes. PSMD was associated with WMH across all regions, and correlations were not significantly stronger in corresponding regions (e.g. frontal PSMD, frontal WMH) compared to non-corresponding regions. PSMD outperformed all four conventional SVD markers and MD in predicting cognition, but was comparable to GM and WM volumes. Discussion: PSMD was robustly associated with established SVD markers. This new measure appears to be a marker of diffuse brain injury, largely due to vascular pathology, and may be a useful and convenient metric of overall cerebrovascular burden.